Study of Fuzzy Distance Measure and Its Application to Medical Diagnosis - Taruna, -; Arora, H D; Kumar, Vijay (Informatica, 2021)
Vagueness is an integral part of different perceptions around the world. Entropy underlies the evaluation of questionable data first presented by Shannon [1] to indicate the degree of skepticism in the probable spread. Fuzzy data measures are widely used in decision-making areas. The Jensen-Shannon difference is a useful measure of distance in the space of probability distribution. In this present correspondence we have a method for estimating the difference between two spectral sets. Investigations of their comprehensive properties for their legitimacy are also mentioned. The numerical controls are listed, which illustrate the proposed technique for solving large decision making problems in fuzzy conditions.